Barriers and facilitators of mental health programmes in primary care in low-income and middle-income countries. (January 2020) - Esponda, Georgina Miguel; Hartman, Sarah; Qureshi, Onaiza; Sadler, Euan; Cohen, Alex; Kakuma, Ritsuko
Summary: Integration of services into primary health care for people with common mental disorders is considered a key strategy to improve access to mental health care in low-income and middle-income countries, yet services at the primary care level are largely unavailable. We did a systematic review to understand the barriers and facilitators in the implementation of mental health programmes. We searched five databases and included studies published between Jan 1, 1990, and Sept 1, 2017, that used qualitative methods to assess the implementation of programmes for adults with common mental disorders at primary health-care settings in low-income and middle-income countries. The Critical Appraisal Skills Programme Qualitative Checklist was used to assess the quality of eligible papers. We used the so-called best fit framework approach to synthesise findings according to the Consolidated Framework for Implementation Research. We identified 24 papers for inclusion. These papers described the implementation of nine programmes in 11 countries. Key factors included: the extent to which an organisation is ready for implementation; the attributes, knowledge, and beliefs of providers; complex service user needs; adaptability and perceived advantage of interventions; and the processes of planning and evaluating the implementation. Evidence on implementation of mental health programmes in low-income and middle-income countries is scarce. Synthesising results according to the Consolidated Framework for Implementation Research helped to identify key areas for future action, including investment in primary health-care strengthening, capacity building for health providers, and increased support to address the social needs of service users.